Cereal grain harvesting and post-harvest machinery in Nepal: A national value chain study - Supetran, Jay P.; Acharya, Jeewan; Chalise, Pushpa Raj; Rauniyar, Ravi Prakash; Justice, Scott; Krupnik, Timothy J. (Cereal Systems Initiative for South Asia, 2021)
The agriculture sector in Nepal constitutes almost 30% of the country’s GDP and contributes 21% of employment in the country. Rice is the main crop with an average production of 3.4 metric tonnes (Mt) per hectare while wheat averages 1.6 Mt per hectare. The mechanization of harvesting is one of the main policies pursued by the Government of Nepal for agricultural modernization. This report provides an overview of the value chains of rice, wheat and maize harvesting equipment available in Nepal, from manufacturing and importing of machines to farm-level service provision. It covers a number of grain-harvesting machines and equipment and their use in Nepal’s Terai southern plains, particularly in selected districts in Parasi, Rupandehi, Kapilvastu, Banke, Bardiya in Lumbini province and Kailali in Sudurpashchim province and their associated value chains in Kathmandu and abroad.